Adrenal Myelolipoma: Diagnosis and Management - Daneshmand, Siamak; Quek, Marcus L (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Adrenal myelolipomas are benign lesions that contain hematopoietic and fatty elements. They are usually hormonally inactive and asymptomatic until they reach large sizes.Â With the routine use of cross-sectional imaging, these lesions are now being discovered with increasing frequency. Materials and Methods: We performed a comprehensive review of the literature using the PubMed database containing the key word adrenal myelolipoma. Results: We identified 492 articles written from 1956 to 2006 and reviewed 93 in detail including the authorsâ€™ own experience. In this review, we highlighted the salient diagnostic features of adrenal myelolipomas and offered a guide for management of these benign lesions. Conclusion: Adrenal myelolipomas may grow over time, but they can usually be followed without surgical excision.Â In some cases, very large myelolipomas can present with pain and can be confused with necrotic adrenal carcinomas, thus necessitating their surgical removal.